스마트 교육을 활용한 팀 기반 문제 중심 학습의 효과: 고위험 신생아 간호를 중심으로. - 양 선 이 (Child Health Nursing Research, 2019)
Purpose: This study was conducted to examine the effects of team-based problem-based learning combined with smart education among nursing students. Methods: A quasi-experimental non-equivalent control group, pre-posttest design was used. The experimental group (n=36) received problem-based learning combined with smart education and lectures 7 times over the course of 7 weeks (100 minutes weekly). Control group (n=34) only received instructor-centered lectures 7 times over the course of 7 weeks (100 minutes weekly). Data were analyzed using the χ² test, the Fisher exact test, and the independent t-test with SPSS for Windows version 21.0. Results: After the intervention, the experimental group reported increased learning motivation (t=2.70, p=.009), problem-solving ability (t=2.25, p=.028), academic self-efficacy (t=4.76, p<.001), self-learning ability (t=2.78, p<.001), and leadership (t=2.78, p=.007) relative to the control group. Conclusion: Team-based problem-based learning combined with smart education and lectures was found to be an effective approach for increasing the learning motivation, problem-solving ability, academic self-efficacy, self-learning ability, and leadership of nursing students.